2010
DOI: 10.3389/fphys.2010.00153
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Membrane Lateral Organization

Abstract: Shortly after the elucidation of the very basic structure and properties of cellular membranes, it became evident that cellular membranes are highly organized structures with multiple and multi-dimensional levels of order. Very early observations suggested that the lipid components of biological membranes might be active players in the creation of these levels of order. In the late 1980s, several different and diverse experimental pieces of evidence coalesced together giving rise to the lipid raft hypothesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 135 publications
(157 reference statements)
1
31
1
Order By: Relevance
“…Animal glycosphingolipid with a monosaccharide headgroup is much bulkier than phospholipid ones and occupies a larger volume, as proposed by theoretical calculations of the minimum energy conformation, which results in spontaneous membrane curvature (25). According to these predictions, ganglioside phase separation in model membrane depends on the surface area occupied by the oligosaccharide chain that is usually directly correlated with the number of sugar residues (121)(122)(123).…”
Section: Free and Conjugated Phytosterols Exhibit Various Abilities Tmentioning
confidence: 86%
See 1 more Smart Citation
“…Animal glycosphingolipid with a monosaccharide headgroup is much bulkier than phospholipid ones and occupies a larger volume, as proposed by theoretical calculations of the minimum energy conformation, which results in spontaneous membrane curvature (25). According to these predictions, ganglioside phase separation in model membrane depends on the surface area occupied by the oligosaccharide chain that is usually directly correlated with the number of sugar residues (121)(122)(123).…”
Section: Free and Conjugated Phytosterols Exhibit Various Abilities Tmentioning
confidence: 86%
“…Multiple roles for lipids in determining membrane order were thus emphasized and encompassed their tendency to phase separation and organization of biological membranes (25). However, all of these studies were performed on model and animal systems, where the lipid diversity is considerably lower than in plants.…”
mentioning
confidence: 99%
“…However, to date, the lipid constituents of PD have not been identified, although research on biological membranes has unequivocally demonstrated that lipids can form functional units capable of modulating membrane organization, protein partitioning, and cellular functions (Lingwood and Simons, 2010;Sonnino and Prinetti, 2010;Munnik and Nielsen, 2011;Bigay and Antonny, 2012;Barrera et al, 2013;Li et al, 2014). Furthermore, the potential for membrane lipids to contribute to the regulation of intercellular communication in plants has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Not only proteins but also lipids are laterally organized within the plane of the membrane and contribute to the formation, dynamics, and function of microdomains (Lingwood and Simons, 2010;Sonnino and Prinetti, 2010;Schäfer et al, 2011;van den Bogaart et al, 2011;Contreras et al, 2012). In plants, a compelling example of membrane functional subcompartmentalization is illustrated by the specialization of the endoplasmic reticulum (ER) and the plasma membrane (PM) at sites of cell-to-cell junctions, called plasmodesmata (PD) (Maule, 2008;Tilsner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…GSLs participate as driving forces in the formation of membrane microdomains and exert specifi c functions related to their physicochemical characteristics through GSL-protein interactions in those domains (87)(88)(89)(90)(91). GSLs preferentially distribute to phase-separated microdomains in the outer leafl et of the plasma membrane, which are suggested to operate as attachment platforms for host pathogens and their toxins on epithelial cells ( 57,92,93 ) to gain entry into cells and retrograde routing to intracellular targets in the cytosol ( 35,56,94 ).…”
Section: Statistics Of Lipid Distribution In Drm and Nondrm Fractionsmentioning
confidence: 99%